Re-evaluating the Legal and Institutional Complications Affecting the Protection of Women's Rights in Cameroon: The Need to Remedying the Odds - Nguindip, Nana Charles (Pancasila and Law Review, 2024)
Several complex legal and institutional issues beset preserving women’s rights in Cameroon. Women’s rights refer to a wide range of ideals and entitlements intended to guarantee gender equality and encourage women’s full involvement and empowerment in all spheres of society. These rights include freedom from violence, equality, education, health, and body autonomy, among other things. However, even with the modern conception and advancement of today's society, women continue to be treated inhumanely, uncaringly, and pitilessly, thereby affecting their status and rights acquired in today´s society, with the numerous legal instruments wavering from the Universal Declaration of Human Rights, the Convention on the Elimination of all Forms of Discrimination Against Women, the Maputo Protocol, the African Charter on the Welfare of the Child, and hosts of other condemning the illegal practices experienced by women on the international scene. The increase in violations continues to be rampant. With all the praiseworthy struggles instigated and affected by these instruments, the degree of violation of women's rights is increasing and increasing in Cameroon. Women continue to experience violations of their rights, especially those related to Female Genital Mutilation, Sexual Abuse, Rape, widow practices, and many other harmful practices. The query one would be posing here is in searching why Cameroon is considered a State of Law, devouring great efforts in certifying that women anguishing from the effect of violence should be protected, continue to experience an increase in cases of women's rights violations. In this vane, it will be sufficient for us to assess the various legal and institutional dispositions put in place by the State of Cameroon in handling cases of violence done against women. It is surprising that with all the laws initiated by the State of Cameroon from the Constitution, the Penal Code, the Labour Code, the Civil Status Registration Ordinance, and the Civil Code enacted to deal with cases of violence done on Women, there exists no concrete and concise law handling matters of violence against women. The situation of child marriage, Female Genital Mutilation, Breast Ironing, Widow Practices, and Property Discrimination continue to be a nightmare and a pandemic to eradicate in the country, irrespective of the efforts introduced by competent authorities. There is a need to redress the situation for a better protective climate for women and their societal statuses.